Evaluation of axle load increasing on a monumental masonry arch bridge based on field load testing. (30th July 2016) - Ataei, Shervan; Jahangiri Alikamar, Meysam; Kazemiashtiani, Vahid
Highlights: Capacity assessment of a 80 years old masonry arch bridge. Performing the displacement measurement of the main span with the length of 40 m and height of 30 m with the precision of 0.01 mm. Finite element model updating based on the displacement measurement results. Computing the dynamic impact factor based on the measurement results. Assessment the potential of axle load increasing based on the updated finite element model and the RING software and comparing their results. Abstract: The importance and long serviceability period of a curved-in-plan masonry arch bridge, and the demand for allowable axle load increasing from 200 to 250 kN, convinced the authors to thoroughly assess the structure under the current standard loading conditions. Through the process of this research, the structure was modeled by taking advantage of the finite element method which accompanied by the model calibration using the obtained results of a predesigned field test, in which the precision of displacement measurement at the middle of main arch (with the height of 30 m from the riverbed) was 0.01 mm. By considering the dynamic impact factor resulted from the field test, the four plastic hinges mechanism and the serviceability limit state have been applied. Consequently, the ultimate adequacy factors of the bridge were resulted by the calibrated finite element model and the RING software. A reasonable agreement between the results was observed that assured the serviceability of the bridge for the current loading condition and even higher up to 250 kN.